Synthesis and biological studies of nickel(II) complexes of thiosemicarbazones / S Savina Savir - S Savina , Savir (2021)
Eleven Schiff base ligands have been prepared from the condensation of N3-substituted thiosemicarbazide with fluorene-2-carboxaldehyde (L1-L3), 2,3,4- trihydroxybenzaldehyde (L4-L7) and 2,5-dihydroxybenzaldehyde (L8-L11). Their corresponding nickel complexes have been synthesized with two general formulations of [Ni(L)2] (1-3) (where L= L1-L3) and [Ni(L)PPh3] (4-11) (where L= L4-L11). The compounds were characterised by FT-IR, 1H NMR, 13C NMR, and single crystal X-ray diffraction. The results suggested that the thiosemicarbazone ligands behaved as bidentate (L1-L3) and tridentate (L4-L11) ligands which were coordinated to the Ni(II) ion via their N,S atoms displaying a square planar geometry (1-3) and their O,N,S atoms displaying a distorted square planar geometry (4-11), respectively. Among the compounds tested, ligands L3 and L5, complexes 1 and 4 showed higher cytotoxicity against HCT 116 human colorectal carcinoma cell line than cisplatin. It is noteworthy that ligands L6, L7 and L8 showed higher cytotoxic activity against PC-3 human prostate cancer cell line than cisplatin. In addition, complexes 2, 3, 5 and 6 exhibited moderate in vitro antimalarial activity. In general, the antimalarial activity of the compound increases as the size of the substituent increases. However, this may not always be the case as anomalies in trend may occur. Our findings revealed that complex 6 displayed the highest antimalarial activity probably due to the more hydrophobic substituent attached at the N(3) position.